POWER STAKEHOLDER DALAM BISNIS - Hasan, Ali (Wahana Informasi Pariwisata : MEDIA WISATA, 2017)
The purpose of the literature review is to explain that stakeholder theories have the right role in the production of business and stakeholder values, the enhancement of stakeholder voices and the advocacy of stakeholders. The focus is on normative theory, the dimensions of stakeholder theory and business performance. Discussion of stakeholder theory is done descriptively in relation to power, legitimacy and their urgency related to stakeholder type in influencing company performance especially in maximizing value and financial performance of company. The stakeholder concept has gained legitimacy among academics in various fields. stakeholder theory will provide benefits in relationships if understanding and integration of stakeholder concepts in management perceptions that their existence has a positive power in build of corporate advantage. Keywords : Stakeholder power, Business and Management